1999
DOI: 10.1111/j.1469-7793.1999.0791p.x
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin‐like peptides depolarize rat hippocampal interneurones through interaction with subtype 2 bombesin receptors

Abstract: Whole‐cell patch‐clamp recordings were made from visually identified hippocampal interneurones in slices of rat brain tissue in vitro. Bath application of the bombesin‐like neuropeptides gastrin‐releasing peptide (GRP) or neuromedin B (NMB) produced a large membrane depolarization that was blocked by pre‐incubation with the subtype 2 bombesin (BB2) receptor antagonist [D‐Phe6,Des‐Met14]bombesin‐(6‐14)ethyl amide. The inward current elicited by NMB or GRP was unaffected by K+ channel blockade with external Ba2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…Within the brain, GRPR is highly expressed in the cell bodies and dendrites of neurons in areas including the dorsal hippocampus and lateral amygdala [23]. Hippocampal GRPRs might be activated by the mammalian bombesin-like peptide GRP released from excitatory neurons [14,21]. GRPR activation might in turn lead to activation of intracellular signaling cascades including the phospholipase C/protein kinase C and MAPK pathways [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the brain, GRPR is highly expressed in the cell bodies and dendrites of neurons in areas including the dorsal hippocampus and lateral amygdala [23]. Hippocampal GRPRs might be activated by the mammalian bombesin-like peptide GRP released from excitatory neurons [14,21]. GRPR activation might in turn lead to activation of intracellular signaling cascades including the phospholipase C/protein kinase C and MAPK pathways [24].…”
Section: Discussionmentioning
confidence: 99%
“…The GRPR is member of the bombesin-like peptide receptor subfamily of G-protein coupled receptors that is activated by the amphibian peptide bombesin or its mammalian counterpart gastrin-releasing peptide (GRP) (for a recent review, see [20]). In the brain, GRP is proposed to be released from excitatory neurons in brain areas including the dorsal hippocampus and bind to GRPRs expressed on the postsynaptic membrane [14,21]. We have previously shown that systemic administration of the GRPR antagonist [D-Tpi 6 , Leu 13 c(CH 2 NH)-Leu 14 ] bombesin (6-14) (RC-3095) impairs aversive memory without affecting nonaversive memory in rats [17].…”
Section: Introductionmentioning
confidence: 98%
“…Previous experiments have revealed that NT increases the firing rate of DAergic neurons by activating nonselective cationic conductances (Seutin et al, 1989;Mercuri et al, 1993;Farkas et al, 1996). In addition to NT receptors, it is known that other G q -coupled receptors can enhance Ca 2ϩ -activated nonselective cationic conductances through an IP 3 -and Ca 2ϩ -dependent signaling pathway Congar et al, 1997;Lee et al, 1999).…”
Section: Mechanism Mediating the Excitatory Effect Of Nt On Daergic Nmentioning
confidence: 99%
“…Indeed, Shumyatsky et al (2002) demonstrated that GRP receptors are located on GABAergic interneurons within the BLA and that excitation of these interneurons increases inhibition of principle neurons. Similarly, GRP was found to depolarize hippocampal interneurons in vitro, resulting in an increase in frequency and amplitude of spontaneous inhibitory post-synaptic currents (Lee et al 1999), while Andrews et al (2000) showed that GRP increases extracellular levels of GABA in the hippocampus through stimulation of BB 2 receptors. Moreover, Dantas et al (2006) found that, at high doses (10 μg/side), the post-training administration of RC-3095 to the dorsal hippocampus enhanced 24 h memory for inhibitory avoidance training, and this enhancement was prevented by a pretraining infusion of an otherwise inert dose of the GABA A receptor agonist muscimol.…”
Section: Discussionmentioning
confidence: 98%